2019
DOI: 10.32872/cpe.v1i1.32605
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Cognitive Model of Depression: The Role of Expectations

Abstract: The cognitive model of depression was highly stimulating for a better understanding and development of treatment for depression. However, the concept of “cognition” is rather broad and unspecific, and we suggest to focus on the cognitive subset of expectation. We conducted a narrative review on the role of expectations, and present an expectation-focused model of explaining why depression tends to persist despite the occurrence of positive events. Several results from basic neuroscience to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
75
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(80 citation statements)
references
References 56 publications
3
75
0
2
Order By: Relevance
“…This is where the idea of cognitive immunisation comes into play: According to Rief et al (2015), cognitive immunisation refers to the very process of reappraising new information in such a way that the discrepancy between the prior belief and new information is reduced. It has been suggested that this cognitive reappraisal leads to sustained negative expectations that become immune to belief updating and learning from new experience (Kube et al, 2020;Rief & Joormann, 2019). In a series of experimental studies, we confirmed this hypothesis by first demonstrating that people with depression maintained negative expectations for their performance despite positive performance feedback, whereas healthy people adjusted their expectation in accordance with the positive feedback (Kube, Rief, Gollwitzer, Gärtner, et al, 2019a, b, c;Kube, Rief, Gollwitzer, et al, 2018).…”
Section: Supplementary Informationsupporting
confidence: 74%
“…This is where the idea of cognitive immunisation comes into play: According to Rief et al (2015), cognitive immunisation refers to the very process of reappraising new information in such a way that the discrepancy between the prior belief and new information is reduced. It has been suggested that this cognitive reappraisal leads to sustained negative expectations that become immune to belief updating and learning from new experience (Kube et al, 2020;Rief & Joormann, 2019). In a series of experimental studies, we confirmed this hypothesis by first demonstrating that people with depression maintained negative expectations for their performance despite positive performance feedback, whereas healthy people adjusted their expectation in accordance with the positive feedback (Kube, Rief, Gollwitzer, Gärtner, et al, 2019a, b, c;Kube, Rief, Gollwitzer, et al, 2018).…”
Section: Supplementary Informationsupporting
confidence: 74%
“…Several recent theoretical models have emphasized the role of prior expectations in depression. For example, it has been proposed that the cognitive theories of depression should focus more on the role of negative expectations and the reasons why such expectations are not being efficiently updated in light of disconfirming evidence (Rief & Joormann, 2019). A recent account of cognitive process in depression has proposed that depression is related to increased prior beliefs that negative events will happen which are not optimally updated thus creating a negative feedback loop (Kube, Schwarting, Rozenkrantz, Glombiewski, & Rief, 2019).…”
Section: Implications For Cognitive Theories Of Depressionmentioning
confidence: 99%
“…Cognitive reappraisal of disconfirmatory evidence is an additional factor that has been discussed as a contributor to the maintenance of dysfunctional beliefs (Rief & Glombiewski, 2016; Rief et al, 2015; Rief & Joormann, 2019). In particular, it has been suggested that people with mental disorders are prone to devaluing positive information that disconfirms disorder-specific negative beliefs by post hoc questioning of its credibility or considering it to be an exception rather than the rule.…”
Section: Factors Contributing To Anomalies In Belief Updatingmentioning
confidence: 99%